MSBNx: A Component-Centric Toolkit for Modeling and Inference with Bayesian Networks - Horvitz, Eric; Hovel, David; Kadie, Carl (2001)
We review the functionality of a modular, component-based tool kit for Bayesian network development and inference. Beyond its operation as a standalone modeling and inference environment, MSBNx facilitates the development of standalone applications by providing a set of run-time components that provide Bayesian reasoning services when integrated into other programs. MSBNx inferential operations provide both inference about states of inference and about the value of information for unobservered evidence. The services and modeling environment supports both diagnostic and troubleshooting mingles observations and repair operations. MSBNx facilitates the development and use of new add-in components. The modeling environment provides a means for assessing distinctions and beliefs, and special interfaces and tools for representing the asymmetric nature of probability distributions.